Effects of range condition on the temporal diet selection by goats in steppe rangelands of Iran - N. Baghestani-Maybodi; M. Jankju-Borzelabad; M. Taghi Zare (Desert, 2008)
One of the key factors in managing a rangeland is to determine the relative preference of its major plant species by thegrazing livestock. Preference value of each plant species is affected by plant type, companion plants, availability byanimals, phenological stage, climate condition, and the livestock species. We investigated the grazing behaviour of anative goat (Garizi) in the steppe rangelands of Iran, from May to November 2004. The study was conducted within oroutside of an enclosure, representing a Good Condition (GC) or a Poor Condition (PC) rangeland, respectively. Flocks ofsix goats were selected randomly and their grazing behaviour was monitored by chronometers. Grazing preference wasconsidered as the time goats had spent for grazing each plant species. The grazing season was divided into 4 grazingperiods, 45 days each. Data recording in the GC and PC sites was repeated 3 times during each grazing period. Theexperiment was designed as the completely randomized blocks. In the GC site, grazing pressure on the perennial grassStipa barbata and the perennial chenopod Salsola rigida was low at the beginning of the grazing period, but it wasincreased towards the end of the grazing season. In the PC site, the main grazing pressure was on noxious plants such asScariola orientalis, Launaea acanthoides, and Cousinia deserti. For both GC and PC sites, the time of grazing hadsignificant influences on relative abundances of annual plants and plant litter, which subsequently changed diet selectionby the Garizi goat. One of the key factors in managing a rangeland is to determine the relative preference of its major plant species by thegrazing livestock. Preference value of each plant species is affected by plant type, companion plants, availability byanimals, phenological stage, climate condition, and the livestock species. We investigated the grazing behaviour of anative goat (Garizi) in the steppe rangelands of Iran, from May to November 2004. The study was conducted within oroutside of an enclosure, representing a Good Condition (GC) or a Poor Condition (PC) rangeland, respectively. Flocks ofsix goats were selected randomly and their grazing behaviour was monitored by chronometers. Grazing preference wasconsidered as the time goats had spent for grazing each plant species. The grazing season was divided into 4 grazingperiods, 45 days each. Data recording in the GC and PC sites was repeated 3 times during each grazing period. Theexperiment was designed as the completely randomized blocks. In the GC site, grazing pressure on the perennial grassStipa barbata and the perennial chenopod Salsola rigida was low at the beginning of the grazing period, but it wasincreased towards the end of the grazing season. In the PC site, the main grazing pressure was on noxious plants such asScariola orientalis, Launaea acanthoides, and Cousinia deserti. For both GC and PC sites, the time of grazing hadsignificant influences on relative abundances of annual plants and plant litter, which subsequently changed diet selectionby the Garizi goat.